2007
DOI: 10.1186/1475-925x-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Current devices for measuring muscle contraction in vivo have limited accuracy in establishing and re-establishing the optimum muscle length. They are variable in the reproducibility to determine the muscle contraction at this length, and often do not maintain precise conditions during the examination. Consequently, for clinical testing only semi-quantitative methods have been used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Previous studies in neuroscience and biomedical engineering have acknowledged that ERP function morphology may change over the course of a task. However, most prior work has focused on controlling for longitudinal trends (Gasser et al, 1983; Turetsky et al, 1989) rather than modeling them; the few works on modeling longitudinal trends have been limited to parametric forms (Rossi et al, 2007; De Silva et al, 2012). We will build our proposed MD-FPCA on data produced by the novel meta-preprocessing step, MAP-ERP, capturing the continuum of longitudinal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in neuroscience and biomedical engineering have acknowledged that ERP function morphology may change over the course of a task. However, most prior work has focused on controlling for longitudinal trends (Gasser et al, 1983; Turetsky et al, 1989) rather than modeling them; the few works on modeling longitudinal trends have been limited to parametric forms (Rossi et al, 2007; De Silva et al, 2012). We will build our proposed MD-FPCA on data produced by the novel meta-preprocessing step, MAP-ERP, capturing the continuum of longitudinal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a significant difference in knee flexion joint angle between the conditions VJFR & HJFR in both jumping and landing phase is a novel finding suggesting that trained athletes may perform VJFR and HJFR with similar knee flexion joint angle. Nagano et al (2007) using computer simulation found that the magnitude of knee flexion joint angle was similar between horizontal and vertical jumps [ 38 ]. In contrast, Fukashiro and colleagues (2005) reported that joint kinematics of the hip, knee and ankle were similar between standing horizontal jump and standing vertical jump during push-off.…”
Section: Discussionmentioning
confidence: 99%
“…Within the basal segments (1-6), the largest difference between the mean T max and the segmental T max happened at segment 2. Within the midwall segments (7)(8)(9)(10)(11)(12), the largest difference was at segment 9, and within apical segments (13)(14)(15)(16), the largest difference was at segment 14. It seems that at these segments (2, 9, and 14) larger errors happen in geometry approximation and fiber orientations in the LV model.…”
Section: Rationale For Segmental Variation Of T Max In the Leftmentioning
confidence: 94%
“…Abnormal myocardial stress leads to hypertrophy of the left ventricle (LV) [10]. However, experimental invasive determination of myocardial stress is not currently a reliable option because errors inherent to the experimental methods are so large that they make the measurements unreliable [11,12].…”
Section: Introductionmentioning
confidence: 99%